CHALLENGES OF LEARNING ENGLISH AS A SECOND LANGUAGE - Gaipova, Nilufarkhan (Educational Research in Universal Sciences, 2023)
This article discusses about the challenges of learning English as a second language, nowadays English is getting more sustainable than in the past, in my opinion it’s case is developing century and intelligence of young generation.